Micro Housing Finance Corporation - Niendorf, Elisabeth; Milap, Akshay; Mendonca, Valerie; Kathuria, Ajay Kumar; Karna, Amit (London : Indian Institute of Management, Ahmedabad, 2020)
This case describes the evolution of the Micro Housing Finance Corporation (MHFC), a player in the informal housing sector in India. From being a new entrant that offered micro home loans to the financially excluded lower-income families of urban India in 2006, MHFC had grown to offer 18,000 loans per year that were worth INR 8 billion, with an average ticket size of INR 0.43 million (USD 6000). With a 53.5% purchasable equity stake in MHFC, the co-founder Chopra and his team had to make some decisions. Should the company onboard a new social investor? Or should it bring on the more readily available and capital-rich private equity investors who were interested in the lucrative prospects of the microfinance housing sector? The case discussion has two key objectives: (1) to understand the entire entrepreneurial journey of a group of entrepreneurs and how they plan to exit the venture, and (2) to enable a classroom discussion on how to develop a business model from scratch, obtain funding, achieve scale and then exit.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Housing -- Finance -- Case studies